2015
DOI: 10.1183/13993003.01288-2015
|View full text |Cite
|
Sign up to set email alerts
|

Gaining insights into pulmonary hypertension in respiratory diseases

Abstract: @ERSpublications Pulmonary hypertension associated with respiratory disease is a difficult to manage condition with significant burden http://ow.ly/S1COQPulmonary hypertension (PH) associated with respiratory diseases, group 3 in the current classification [1], is one of the most frequent presentations of PH. Chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF) are the two most common respiratory disorders associated with PH. In these conditions the presence of PH is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] PH in COPD and ILD increases symptomatic burden, costs, and reduces survival. [1][2][3][4][5][6][7][8][9][10] Although not extensively studied in the WHO Group III PH population, many providers are using pulmonary arterial hypertension (PAH)-specific therapy for WHO Group III PH patients. In fact, a recent study showed 80% of PH referral centers in the USA use PAH-specific therapy in WHO Group III PH patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] PH in COPD and ILD increases symptomatic burden, costs, and reduces survival. [1][2][3][4][5][6][7][8][9][10] Although not extensively studied in the WHO Group III PH population, many providers are using pulmonary arterial hypertension (PAH)-specific therapy for WHO Group III PH patients. In fact, a recent study showed 80% of PH referral centers in the USA use PAH-specific therapy in WHO Group III PH patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 Use of PAH-specific therapy in WHO Group III PH patients is controversial as these medications are only approved for WHO Groups I and IV patients, and there is theoretical concern that the pulmonary vasodilation could result in ventilation perfusion (V/Q) mismatch and subsequently worsen hypoxemia. 10 However, small clinical trials in COPD-PH and ILD-PH patients showed PAH-specific medications were safe, but the therapeutic benefit was unclear. [12][13][14][15][16][17][18][19][20][21] In order to gain better insight into the utility of PAH-specific therapy in WHO Group III PH, we conducted a systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary hypertension (PH) in the setting of chronic lung disease or World Health Organization (WHO) Group 3 PH is the second most common cause of PH after left heart disease. 1,2 Group 3 patients have a high symptom burden 3 and poor long-term outcomes with a median survival of only 2 to 5 years after diagnosis. 2,48 Furthermore, there are no approved treatments for Group 3 PH, and pulmonary vasodilator therapy does not improve exercise capacity or reduce symptom burden.…”
mentioning
confidence: 99%
“…Pulmonary vascular abnormalities, as shown by alterations in vessel structure, abnormal cell growth, endothelial dysfunction and resistance to apoptosis, are characteristic features in COPD [4, 5]. An altered pulmonary vascular function in COPD patients may predispose to pulmonary hypertension, which is associated with adverse outcomes [6]. Growing evidence suggests that endothelial cell damage found in pulmonary vessels of COPD patients is an initial and important triggering factor that promotes pulmonary vascular remodelling [5].…”
Section: Introductionmentioning
confidence: 99%